Slow sulfide donor GYY4137 differentiates NG108-15 neuronal cells through different intracellular transporters than dbcAMP - Kubickova, J; Hudecova, S; Csaderova, L; Soltysova, A; Lichvarova, L; Lencesova, L; Babula, P; Krizanova, O (Neuroscience, 2016)
Cellular differentiation is the process, by which a cell changes from one cell type to another, preferentially to the more specialized one. Calcium fluxes play an important role in this action. Differentiated NG108-15 or PC12 cells serve as models for studying neuronal pathways. NG108-15 cell line is a reliable model of cholinergic neuronal cells. These cells differentiate to a neuronal phenotype due to the dibutyryl cAMP (dbcAMP) treatment. We have shown that a slow sulfide donor - GYY4137 - can also act as a differentiating factor in NG108-15 cell line. Calcium is an unavoidable ion required in NG108-15 cell differentiation by both, dbcAMP and GYY4137, since cultivation in EGTA completely prevented differentiation of these cells. In this work we focused primarily on the role of reticular calcium in the process of NG108-15 cell differentiation. We have found that dbcAMP and also GYY4137 decreased reticular calcium concentration by different mechanisms. GYY4137 caused a rapid decrease in type 2 sarco/endoplasmic calcium ATPase (SERCA2) mRNA and protein, which results in lower calcium levels in the endoplasmic reticulum compared to the control, untreated group. The dbcAMP revealed rapid increase in expression of the type 3 IP3 receptor, which participates in a calcium clearance from the endoplasmic reticulum. These results point to the important role of reticular calcium in a NG108-15 cell differentiation.
Keywords: Neurons; dibutyryl cyklický AMP; messenger RNA; IP(3) receptors; nádorové buněčné linie; Mice, Inbred BALB C; Cell Differentiation; inositol-1,4,5-trisfosfát - receptory; SERCA2; Organothiophosphorus Compounds; Inositol 1,4,5-Trisphosphate Receptors; vápník; Hydrogen Sulfide; NG108-15 cell line; sulfan; Mice; Cell Line, Tumor; GYY4137; organothiofosforové sloučeniny; Calcium; sarkoplazmatická Ca2+-ATPáza; RNA, Messenger; zvířata; Sarcoplasmic Reticulum Calcium-Transporting ATPases; neurony; myši inbrední BALB C; morfoliny; dbcAMP; myši; neuronal differentiation; buněčná diferenciace; Bucladesine; Morpholines; Animals